2008
DOI: 10.1161/circulationaha.107.711507
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Associations Between Chronic Periodontitis/Edentulism and Risk of Coronary Heart Disease

Abstract: Background-Several epidemiological studies have suggested periodontitis as a risk factor for coronary heart disease (CHD), but results have been inconsistent. Methods and Results-We evaluated the association between clinical and radiographic measures of periodontitis, edentulism, and incident CHD (angina, myocardial infarction, or fatal CHD) among 1203 men in the VA Normative Aging and Dental Longitudinal Studies who were followed up with triennial comprehensive medical and dental examinations up to 35 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
226
2
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(256 citation statements)
references
References 38 publications
14
226
2
14
Order By: Relevance
“…Common risk factors such as diabetes mellitus, smoking, genetics, stress, depression, physical inactivity and obesity make it difficult to positively associate periodontitis and CHD (10,11). However, studies have shown such association regardless of common risk factors to be possible (12)(13)(14). Moreover, recent meta-analyses established periodontitis as a risk factor, or as a marker independent of traditional CAD risk factors, for CHD with relative risks ranging from 1.24 to 1.35 (15).…”
Section: Materijali I Postupcimentioning
confidence: 99%
“…Common risk factors such as diabetes mellitus, smoking, genetics, stress, depression, physical inactivity and obesity make it difficult to positively associate periodontitis and CHD (10,11). However, studies have shown such association regardless of common risk factors to be possible (12)(13)(14). Moreover, recent meta-analyses established periodontitis as a risk factor, or as a marker independent of traditional CAD risk factors, for CHD with relative risks ranging from 1.24 to 1.35 (15).…”
Section: Materijali I Postupcimentioning
confidence: 99%
“…Periodontitis is the leading cause of tooth loss worldwide (Petersen et al, 2005;Pihlstrom et al, 2005). Furthermore, it has been proven to be a significant risk factor of systematic diseases, including coronary heart disease (Dietrich et al, 2008), stroke (Sfyroeras et al, 2012), obesity (Suvan et al, 2011), atherosclerosis (Tonetti, 2009), preterm birth and low birth weight in infants (Rakoto-Alson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In many epidemiological studies, periodontitis was proven to play important roles in initiation and progression of CVD, [69,70] by chronic infection on the blood vessels [20][21][22][23][24][25][26][27][28][29] or by the elevation of body�s CRP level. [29][30][31][32][33][34][35][36][37][38][39] The prevalence of chronic periodontitis was very high among populations, especially in chronic form.…”
Section: Discussionmentioning
confidence: 99%
“…[75] Chronic infection was known to be able to cause endothelial dysfunction. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] PG�s fimbriae secretes protein, called gp130, [83] which facilitate PG to invade EC and trigger celluler immune response. [84] The host will secrete TNF, [85] IL-1, IL-6, IL-10, and IL-12 [86][87][88] by TLR�s stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation